1982
DOI: 10.1007/bf02636050
|View full text |Cite
|
Sign up to set email alerts
|

Oil from deep water fish species as a substitute for sperm whale and jojoba oils

Abstract: The lipid fraction of the deep water fish species orange roughy (Hoplostetbus atlanticus), black oreo (Allocyttus sp.) and small spined oreo (Pseudocyttus maculatus) had wax esters with even carbon numbers over the range C30 to C46 as the major components. The component acids and alcohols of the wax ester fraction were analyzed by gas liquid chromatography and compared with those of jojoba and sperm whale oils. Orange roughy oil was refined and deodorized and its chemical, physical and mechanical properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The high monoene levels in the WE of the myctophid lipids was similar to that of other deep-sea fish species containing WE as major components. The same trend has been noted in reports on the lipids of deep-sea fishes (Mori et al 1966, Nevenzel et al 1969a, Sargent et al 1977, Hayashi & Takagi 1980, Nevenzel & Menon 1980, Buisson et al 1982, Grigor et al 1983, Sargent et al 1983, Body et al 1985, Takagi et al 1985, Lee & Patton 1989, Bakes et al 1995). Fatty acid composition of TAG, major components for 10 myctophid species which displayed vertical migration…”
Section: Fatty Acid and Fatty Alcohol Compositions Of We Major Composupporting
confidence: 57%
See 1 more Smart Citation
“…The high monoene levels in the WE of the myctophid lipids was similar to that of other deep-sea fish species containing WE as major components. The same trend has been noted in reports on the lipids of deep-sea fishes (Mori et al 1966, Nevenzel et al 1969a, Sargent et al 1977, Hayashi & Takagi 1980, Nevenzel & Menon 1980, Buisson et al 1982, Grigor et al 1983, Sargent et al 1983, Body et al 1985, Takagi et al 1985, Lee & Patton 1989, Bakes et al 1995). Fatty acid composition of TAG, major components for 10 myctophid species which displayed vertical migration…”
Section: Fatty Acid and Fatty Alcohol Compositions Of We Major Composupporting
confidence: 57%
“…Deep-sea teleost fishes often have considerable amounts of wax esters (WE) as a substitute for TAG (Mori et al 1966, Lewis 1967, Nevenzel1969, Nevenzel M i~r Ecol Prog Ser 168: 21-33, 1998, Benson & Lee 1975, Sargent et al 1977, Hayashi & Takagi 1980, Nevenzel & Menon 1980, Buisson et al 1982, Grigor et al 1983, Sargent et a1 1983, Body et al 1985, Takagi et al 1985, Lee & Patton 1989, Bakes et al 1995. Though the results in these papers have described the lipid of deep-sea fishes as contaming high amounts of WE, they have not mentioned the origin of these high WE levels or detailed the reiationship between the tissue WE and habitat.…”
Section: Introductionmentioning
confidence: 99%
“…The oil, protein, moisture and ash contents of the flesh of orange roughy have been previously reported (Vleig, 1983). Also Buisson et al (1982) have examined the properties of the oil. Grigor et al (1983) have studied the composition and location of the oil in the fish.…”
Section: Introductionmentioning
confidence: 99%
“…This fish stores large amounts of wax ester in tissues such as a fat-invested swimbladder, bone, skin (Buisson et al 1982, Grigor et al 1983) and in a fat-infiltrated organ found in the neurocranial cavity (Sargent et al 1983). This fish stores large amounts of wax ester in tissues such as a fat-invested swimbladder, bone, skin (Buisson et al 1982, Grigor et al 1983) and in a fat-infiltrated organ found in the neurocranial cavity (Sargent et al 1983).…”
Section: Introductionmentioning
confidence: 99%